GE_GERICHTE C/118/2010 vom 6. Mai 2016 - GE Cour de justice (2016)
ACTION EN PARTAGE SUCCESSORAL; ENRICHISSEMENT ILLÉGITIME; CONVERSION(CALCUL); RAPPORT DE VALEUR; QUOTE-PART; MASSE SUCCESSORALE | CC.604; CC.626; CO.62